Moderation in Arabic Classical Literature: Qur’anic Teachings on Consumerism and Waste Management - HLM. Mohideen (Jurnal Bahasa Arab, 2025)
This study explores the semantic meaning of the primary Arabic literature, the Qur'an, on moderation, with particular attention to the prohibitions on Israf (luxury) and Tabdhir (waste). It evaluates its relevance to addressing consumerism and waste management in the modern context. Drawing on Qur'anic verses, Prophetic traditions, and Islamic ethical principles such as Mizan (balance), Imarah (stewardship), and Amanah (trust), the research method employed is the study and semantic analysis of the Qur'anic text. The results demonstrate how Islamic teachings construct a holistic framework that integrates moral, spiritual, and ecological responsibilities. The analysis highlights key applications of these principles at the individual, community, and policy levels, including lifestyle moderation, mosque-led environmental initiatives, and the development of Fiqh al-Bī’ah (Islamic environmental jurisprudence) and ecological fatwas. The study examines issues such as food waste, plastic pollution, e-waste, and the fast-fashion culture and illustrates the contemporary relevance of Islamic ethics to global sustainability challenges. Ultimately, this study argues that the Qur'anic vision of moderation and balance provides not only spiritual guidance but also a practical and normative framework that makes a meaningful contribution to the global debate on sustainability, offering an integrated approach that unites ecological responsibility with moral accountability.